-10b+q=s

Simple and best practice solution for -10b+q=s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10b+q=s equation:


Simplifying
-10b + q = s

Solving
-10b + q = s

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1q' to each side of the equation.
-10b + q + -1q = -1q + s

Combine like terms: q + -1q = 0
-10b + 0 = -1q + s
-10b = -1q + s

Divide each side by '-10'.
b = 0.1q + -0.1s

Simplifying
b = 0.1q + -0.1s

See similar equations:

| 3(a+4)=-18 | | 7(x+8)=105 | | 5n^2=0 | | 84+12x+48= | | 16=x-x*0.02*1.19 | | -a^2+9=0 | | 2x^2+14x=7x+49 | | 16*1.19=x-x*0.02 | | 10.12-3m=18 | | 2g-5(9+4g)= | | 4x^5-8x^3=0 | | 3d^2=-75 | | X=-10x+50 | | 15x^2+95x+30=0 | | 2x+12=3*-6 | | 1=6*x^2+5*x | | sx+12=3*-6 | | 3.2m+7.45/3.1=2.06 | | (X+11)(x-1)=0 | | 5x=4y-7 | | 8p+3q=23 | | 20c^2-23c+6=0 | | 6(8-5h)= | | 2x+3q+14=0 | | 15-2x(4-3x)=37 | | u^2-15u+54=0 | | -(n-5)=-2n-2 | | 5x+2=3+8 | | 20x^2-35x-75=0 | | 4x+3=2x+8findx | | 5*x^2-18*x=-13 | | 5p+7=4(4-p) |

Equations solver categories